2021
DOI: 10.1186/s12913-021-07194-6
|View full text |Cite
|
Sign up to set email alerts
|

Observations from the emergency management of dialysis patients evacuated from the US Virgin Islands to Puerto Rico following hurricane Irma

Abstract: Two category 5 hurricanes, Irma and Maria, arrived in the Caribbean in September 2017 in rapid succession. On September 6, Irma devastated the islands of St. Thomas and St. John, in the Virgin Islands of the United States (USVI). Most medical infrastructure was damaged, including hemodialysis facilities, paralyzing dialysis operations. After Irma’s landfall, Puerto Rico served as a safehaven for thousands of displaced and repatriated persons from the impacted islands. These included a cohort of 129 hemodialysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This challenge has been well documented in regions struck by Hurricanes Katrina, Sandy, and Maria and Winter Storm Uri. 7,8,[29][30][31] After Hurricane Katrina in August 2005, 94 dialysis clinics closed for at least 1 week in the Gulf Coast states, including Louisiana, Mississippi, and Alabama. 29 A study investigated the factors associated with missed dialysis sessions after Hurricane Katrina and reported that the probability of missing three or more sessions was greater among those who lived alone before the hurricane's landfall, who did not evacuate before the storm, or who were placed in storm shelters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This challenge has been well documented in regions struck by Hurricanes Katrina, Sandy, and Maria and Winter Storm Uri. 7,8,[29][30][31] After Hurricane Katrina in August 2005, 94 dialysis clinics closed for at least 1 week in the Gulf Coast states, including Louisiana, Mississippi, and Alabama. 29 A study investigated the factors associated with missed dialysis sessions after Hurricane Katrina and reported that the probability of missing three or more sessions was greater among those who lived alone before the hurricane's landfall, who did not evacuate before the storm, or who were placed in storm shelters.…”
Section: Discussionmentioning
confidence: 99%
“…8 In Puerto Rico, the landfall region of Hurricanes Irma and Maria in September 2017 experienced catastrophic damage to most medical infrastructure and paralyzed dialysis operations that resulted in mandatory patient evacuations. 30 Winter storm Uri in 2021 caused mass power outages throughout Texas and affected approximately 54,000 dialysis patients. 31 The Intergovernmental Panel on Climate Change report suggests imminent and increased extreme weather magnitudes, duration, and frequencies with substantial alterations in regional patterns of extreme weather.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation